Intraoperative cell salvage as an effective intervention for postpartum hemorrhage—Evidence from a prospective randomized controlled trial - Lei, Bo; Guo, Min; Deng, Xin; He, Shujun; Lu, Xin; Wang, Yunjuan; Wang, Lei (Frontiers in Immunology, 2022)
Background Postpartum hemorrhage (PPH) is one of the leading causes of maternal mortality. Promptly recovering blood loss is critical for PPH. Intraoperative cell salvage (ICS) is a method to collect and process red blood cells (RBCs) from the blood lost during surgery and transfuse them to the patient’s circulation during or immediately after surgery. Its effectiveness in reducing the demand for allogeneic blood transfusion has been proven, but its effectiveness and safety as a sole treatment for PPH during Cesarean sections are unclear. This is particularly important for patients who cannot or do not want to accept allogeneic blood transfusion. Materials and methods In this prospective randomized controlled study, patients with high risks of PPH were randomized into the ICS group or the control group, receiving ICS or allogeneic RBC transfusion if their hemoglobin level was less than 80 g/L during operation. Data collected include clinical examination, blood cell count, hemoglobin level, coagulation function, and plasma levels of fetal hemoglobin, tissue factor, and alpha-fetoprotein before and after fetal delivery and 0, 2, and 12 h after treatment. Adverse events were recorded. Results A total of 130 patients were enrolled, aged 33 ± 1 years with a mean gestation period of 37 ± 1 week. The most common cause of Cesarean section was placenta previa, followed by twin pregnancy, scarred uterus, preeclampsia, placental abruption, fetal distress, and placenta accreta spectrum. Bleeding amount was similar between the two groups. The ICS group, compared to controls, had more efficient increases in levels of hemoglobin, RBC, and hematocrit (all p < 0.05). Coagulation function was maintained in the ICS group but reduced in controls 24 h after transfusion, indicated by significantly reduced fibrinogen level and prolonged prothrombin time (PT), thrombin time (TT), and activated partial thromboplastin time (aPTT) (all p < 0.05). There was a transient but significant decrease in plasma tissue factor and alpha-fetoprotein levels and an increase in plasma fetal hemoglobin level with ICS treatment in the postpartum period. No adverse event occurred with ICS intervention. Conclusion ICS is an effective and safe intervention for patients with a high risk of PPH during elective or emergency Cesarean section. It can effectively clear tissue factors and alpha-fetoprotein but not fetal hemoglobin.